Fiscal and Monetary Policies Coordination Rwanda Experience - Augustin Ndarihoranye; Gedion Alang’o; Omwono Omwono (RIRAI Publisher, 2020)
This paper attempts to quantify the coordination between monetary and fiscal policies in Rwanda from 2008 to 2018. The paper uses Granger causality test and vector autoregressive (VAR) framework to determine whether these policies are implemented independently and also looks at the extent of their coordination. The empirical results using unstructured VAR model suggest that monetary and fiscal policies interact and are coordinated in Rwanda. The impulse response functions demonstrate significant interaction between monetary and fiscal policy. For instance a positive shock on government expenditure induces an increase in broad money that in turn induces an increase in liquidity in the economy. Finally, the paper recommends that both policies should continue interacting in order to strengthen policy coordination. Therefore, ultimately achieve a stable and low inflation together with high growth.